2013
DOI: 10.1007/s11102-013-0473-5
|View full text |Cite
|
Sign up to set email alerts
|

Is a stable or decreasing prolactin level in a patient with prolactinoma a surrogate marker for lack of tumor growth?

Abstract: The optimal interval for follow-up imaging of patients with prolactinomas is unclear. We wish to determine the likelihood of tumor enlargement in patients with prolactinomas who have a stable or reduced prolactin (PRL) level over time, whether or not they are treated with a dopamine agonist (DA). We identified 80 patients with prolactinomas (34 men, 46 women) who had at least two paired sets of serum PRL levels and pituitary MRIs, 3 or more months apart. Patients with hyperprolactinemia due to drug or stalk ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(10 citation statements)
references
References 19 publications
0
9
0
Order By: Relevance
“…Prolactin release is controlled by prolactininhibiting factors, such as dopamine, which is produced in the arcuate nucleus. 30 As the arcuate nucleus also receives neural inputs from the SFO, autoimmune damage in the SFO might cause dysfunction in the arcuate nucleus and dysregulation of prolactin release. Taken together, in patients with adipsic hypernatremia and prolactin levels <120 ng/ml, potential autoimmunity to the SFO should be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…Prolactin release is controlled by prolactininhibiting factors, such as dopamine, which is produced in the arcuate nucleus. 30 As the arcuate nucleus also receives neural inputs from the SFO, autoimmune damage in the SFO might cause dysfunction in the arcuate nucleus and dysregulation of prolactin release. Taken together, in patients with adipsic hypernatremia and prolactin levels <120 ng/ml, potential autoimmunity to the SFO should be taken into consideration.…”
Section: Discussionmentioning
confidence: 99%
“…The relationship between tumor size and serum PRL level remains controversial. [9] It has been demonstrated that the preoperative PRL level does not correlate with tumor size. Lactotropes and somatotrophs share a common precursor cell; [10] therefore, the overgrowth of precursor cells may lead to GH-PRL mixed adenomas.…”
Section: Discussionmentioning
confidence: 99%
“…At variance, in MP in case of PRL levels Although there is a clear correlation between size of adenoma and PRL levels (57,58,59) before and after treatment, there are cases of discordance between tumor changes and PRL levels during therapy (94). In most of these rare cases, enlargement of MP during DA therapy with stable/reduced PRL levels is mostly related to pituitary hemorrhage (95). The timing of further MRI follow-up after the first performed at 1-3 months should be based on the individual clinical context, including the changes of neuroophthalmological and endocrinological picture, pre-treatment adenoma size, signs of invasiveness, prior surgery, rate of PRL decline and tumor shrinkage on DA treatment, sex, estrogen state, as well as adherence to the medication (96).…”
Section: Follow-up Imagingmentioning
confidence: 99%
“…Enlargement of microP while on DA therapy was reported to be extremely rare (95). This observation has led some experts to recommend not performing follow-up MRI at least for microPs (97) unless PRL rises significantly (e.g., >250 ng/mL), or if severe headache, impairment of visual fields or visual acuity or cranial nerve palsies develop (98,99).…”
Section: Follow-up Imagingmentioning
confidence: 99%
See 1 more Smart Citation